THE QURANIC PERSPECTIVES ON WEALTH INVESTMENT IN REALIZING MAQASHID SHARI'AH - Safrudin Halimy Kamaluddin; Meirison Meirison (al-Afkar, Journal For Islamic Studies, 2021)
Knowledge of the Maqasid of Sharia comes from the texts of the Qur'an and Sunnah, and its roots are deeply rooted in the consciousness of the first generations of Muslims, especially in the first centuries. The verses of the Qur'an are rich in statements of statutory regulations, and the hadiths of the Prophet are full of clarifications of importance arising from the commands and instructions of the Maqashid of Sharia. Text is the first, strongest, and highest way to express the will of Allah S.W.T. Therefore, this study aims to collect "all" explanations regulated in the Qur'an in the field of finance and wealth. Money is useful in realizing four main interests: primary, secondary, and tertiary needs that support each other with problems and Maqashid shari'ah. By conducting a study of the opinions of some scholars through literature studies and qualitative approaches, the principles of Maqashid Sharia in the Qur'an are obtained with various dimensions of interpretation originating from the Sunnah of the Prophet and the opinions of scholars, such as as-Syatibiy, Raisuni, and other scholars. Money is the basis of religion and worship. One of the five pillars is zakat, worship in financial management because other worship will be disrupted without being supported by financial elements. Asset management in Islamic Mashasid is also aimed at various types of investments that bring five benefits to Muslims in multiple activities, including growing wealth for the benefit of the people and preventing environmental damage and global warming that is currently happening. Keywords: Quranic, wealth, maqashid shari'ah